2016
DOI: 10.1021/jacs.6b02632
|View full text |Cite
|
Sign up to set email alerts
|

Design Strategy for High-Performance Dendritic Carbazole-Containing Alkynylplatinum(II) Complexes and Their Application in Solution-Processable Organic Light-Emitting Devices

Abstract: A new class of luminescent dendritic carbazole-containing alkynylplatinum(II) complexes has been synthesized, characterized, and applied as phosphorescent dopants in the fabrication of solution-processable organic light-emitting devices (OLEDs). These complexes exhibit high photoluminescence quantum yields of up to 80% in spin-coated thin films. In addition, the incorporation of carbazole dendrons into the platinum(II) center can significantly suppress intermolecular interactions in solid-state thin films, giv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(57 citation statements)
references
References 81 publications
4
52
0
1
Order By: Relevance
“…It has been noted that the incorporation of carbazole dendrons into the Pt(II) centre can significantly suppress intermolecular interactions in solid-state thin films, giving rise to emission spectra (l max /nm = 512, lifetime = 2.4-2.7 and F = 0.42-0.71 ms) that are similar to those found in solution. 36 Another example of changes in topology altering the emission properties has been demonstrated using the complex 7. Yang et al 37 found a correlation between the topology of the ligand and the T 1 state energy.…”
Section: Platinum(ii) Alkynyl Complexes With C^n^n Pincer Ligandsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been noted that the incorporation of carbazole dendrons into the Pt(II) centre can significantly suppress intermolecular interactions in solid-state thin films, giving rise to emission spectra (l max /nm = 512, lifetime = 2.4-2.7 and F = 0.42-0.71 ms) that are similar to those found in solution. 36 Another example of changes in topology altering the emission properties has been demonstrated using the complex 7. Yang et al 37 found a correlation between the topology of the ligand and the T 1 state energy.…”
Section: Platinum(ii) Alkynyl Complexes With C^n^n Pincer Ligandsmentioning
confidence: 99%
“…34 A series of dendritic carbazole-containing [Pt(N^C^N)(CRCR)] complexes of up to fourth generation 9a-9d (Chart 9) has been reported by Yam et al with high F of up to 80% in thin films and applied as phosphorescent dyes for fabricating highperformance solution-processed OLEDs with peak EQE and CE of up to 10.4% and 37.6 cd A À1 , which is comparable to that of the evaporated devices based on the small-molecule counterparts. 36 The high efficiency is attributed to the presence of carbazole dendrimers that can significantly suppress intermolecular interactions of the complexes in the solid film.…”
Section: Emerging Applicationsmentioning
confidence: 99%
“…Alternatively, development of emissive complex incorporated in a dendritic structure allows controlling both charge transport and light emission in a single material [61]. In this regard, Yam and co-workers reported on a series of dendritic carbazole-based alkynylplatinum(II) complexes with cyclometalated 2,6-bis( N -alkylbenzimidazol-2’-yl)benzene (bzimb) as the N^C^N tridentate ligand [62]. These complexes were found to be highly emissive with PLQYs of up to 0.80 in solid-state thin films.…”
Section: Reviewmentioning
confidence: 99%
“…Phosphorescent transition‐metal complexes have played the vital role in the rapid development of OLEDs, because they can harvest both singlet and triplet excitons to achieve an internal quantum efficiency of 100% owing to the highly efficient spin‐orbit coupling effect induced by heavy‐metal atoms . For example, noble metal‐based phosphors including iridium(III) complexes, platinum(II) complexes, and gold(III) complexes have been widely used in phosphorescent OLEDs (PhOLEDs). However, these noble metals suffer from the low abundance and high cost.…”
Section: Key Performance Of the Devices A–cmentioning
confidence: 99%